Break the strength and ductility trade-off in novel NbC reinforced Fe40.5(CoCr)25Mn17.5Ni10Si5 high entropy alloy - Ali, Naqash; Li, Jiale; Zhang, Liqiang; Zhang, Chaojie; Zhou, Hongwei; Liu, Dongming; Sanaullah, Kiran; Nian, Yi; Cheng, Jinjun (Materials & design, 2024)
[Display omitted] •A novel NbC reinforced Fe40.5(CoCr)25Mn17.5Ni10Si5 HEA was designed.•The microstructure evolution and deformation mechanisms was systematically investigated.•The studied HEA contain chemical short-range order (SRO) domains.•This precipitation strengthen HEA possessed high strength and ductility. In this study, a novel NbC reinforced Fe40.5(CoCr)25Mn17.5Ni10Si5 high entropy alloy (HEA) was designed, which exhibits high strength and ductility at room temperature. This alloy was prepared through hot forging and annealing treatments, which exhibited the FCC microstructure with NbC and discrete nano-sized M23C6 carbides precipitation. The studied HEA retained a tensile strength of 863 MPa, and an outstanding ductility of 58 %. The microstructure evolution and deformation mechanisms were further investigated. The deformation mechanism was mainly governed by nano-scale defect heterogeneity of stacking faults (SFs), deformation twins and dislocations. The improved strength-ductility synergy is attributed to the formation of multiple SFs, deformation twining, dislocation cells, and nano-sized NbC precipitation. Moreover, the TEM observation elucidates the presence of chemical short-range order (SRO) domain in the studied HEA, which also has a major contribution in strength and ductility increment. The present findings shed light on developing the HEAs through proper compositional design and heat treatments, resulting in the combine effect of precipitation strengthening, SFs mediated plasticity, twinning induced plasticity (TWIP), and SRO effect.